Attempting to be active: Self-efficacy and barrier limitation differentiate activity levels of working mothers. (July 2016) - Gierc, Madelaine; Locke, Sean; Jung, Mary; Brawley, Lawrence
Working mothers are less physically active than working women without children and mothers who do not work. The purpose of this study was to examine concurrent self-regulatory efficacy and barriers to physical activity in a sample of working mothers. Women completed a mixed-methods survey which included measures of physical activity, concurrent self-regulatory efficacy, and barriers. Sufficiently active women experienced significantly greater concurrent self-regulatory efficacy and significantly less barrier limitation and frequency. No significant group differences were found for age, domestic duties performed, and children's extracurricular activities. Thematic analysis of barriers revealed six themes of common and unique factors, including limited time and family activities.